Muhammadiyah constitution jihad movement: a case study of the Omnibus Law on job creation - Muhammad Nurul Huda; Hammam Hammam; Suranto Suranto; Herdin Arie Saputra (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2021)
The Omnibus Law on job creation is a government initiative proposal and it has drawn public reactions to polemics of debate. Muhammadiyah as a religious organisation also expressed their objections to the Omnibus Law on job creation. This article is qualitative research that applies NVivio 12 plus to manage the data through crosstab analysis and cluster analysis. This study shows that there are aspects of conflictual relations that give rise to a movement. Muhammadiyah forms a formal or non-formal organization that involves the Law and Human Rights Council (HAM) as well as s a forum of the dean of the law faculty and the head of the law school of Muhammadiyah and Aisyiyah universities. In the concept, of Muhammadiyah emphasizes to synchronise between institutions by prioritizing transparency, making laws severe in their implementation. Muhammdiyah offers three concept points, namely revoking a government regulation in lieu of law (PERPU), delaying its implementation, and revising through public participation.